Female Hedonistic Behavior Questionnaire (FHBQ): Psychometric Properties Based on the Rasch Model - Deviana, Tina; Hayat, Bahrul; Tresniasari, Nia (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2020)
This study aims to develop standard measurement tools from hedonistic behavior using the perspective of the Rasch measurement model. The evaluation of psychometric characteristics conducted in this study (1) to check unidimensionality, (2) testing local independence assumptions, (3) testing scale rating diagnostics, (4) testing item fit, (5) reliability for person and items, and (6) displays the wright map and test information function to compare people and items on the same scale and find out the functioning of the test when given to individuals with the level of trait obtained. The sample in this study were 335 hijab-wearing Muslim women. Rasch analysis results show that the psychometric characteristics obtained are very good and precise, as well as the suitability of the items to the model. With this, the measuring instrument developed by researchers was named the Female Hedonistic Behavior Scale (FHBQ) with 14 valid items from the Rasch rating scale model from the measurement model perspective.